Revitalisasi Pendidikan Kewarganegaraan melalui Nilai-Nilai Hukum Islam Kontemporer - Opy Putri Melani; Anwar Sidik (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study aims to analyze the revitalization of Citizenship Education (Civics) through the integration of contemporary Islamic legal values in strengthening students’ character. Citizenship Education plays a strategic role in shaping responsible, intelligent, and morally grounded citizens; however, it faces significant challenges in the era of globalization and cultural diversity. This research employs a qualitative approach using a literature review method by examining various relevant academic sources. The findings indicate that Islamic legal values such as justice, honesty, responsibility, deliberation, and tolerance are closely aligned with the principles of Pancasila and can enhance the contextual and practical implementation of Citizenship Education. Furthermore, teachers’ roles as role models, supportive educational environments, and innovative teaching methods are essential factors in ensuring successful integration. Despite several challenges, including limited instructional time, lack of teacher training, and differing perspectives among educators, strategic solutions can be implemented through curriculum strengthening, capacity building for teachers, and collaboration among schools, families, and communities. Therefore, integrating Islamic legal values into Citizenship Education is expected to produce a generation that excels intellectually while possessing strong moral and spiritual character.